Determination of Lead (Pb) in Patin Fish Oil (Pangasius hypophthalmus) Using Atomic Absorption Spectrophotometry (AAS) - Azlaini Yus Nasution; Renni Izmi Indriani (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2021)
to chemical contamination due to human activities. Chemical contaminants can come from heavy metals such as lead (Pb). Catfish can be used as a source of fish oil which may also be contaminated with lead metals. This study aims to determine the levels of lead (Pb) heavy metal contamination in the oil extract of catfish (Pangasius hypophthalmus). This research is an experimental laboratory research and the results are presented in descriptive form. The method used is the Atomic Absorption Spectrophotometry (AAS) method. The result of the determination of lead metal content in the catfish oil extract was 0 mg/kg.